82.9k views
3 votes
PLS GIVE FULL EXPLANATION ASAP - class is litterally in an hour

If 9x+2y^2−3z^2=132 and 9y+2y^2−3z^2=−12, then x−y =
(A) 3 (B) 8 (C) 16 (D) 120 (E) 144

1 Answer

5 votes

Answer:

(C) 16

Explanation:

Subtract the second equation from the first equation.

9x + 2y^2 - 3z^2 = 132 minus 9y + 2y^2 - 3z^2 = -12

9x + 2y^2 - 3z^2 = 132

-(9y + 2y^2 - 3z^2 = -12 )

This will change all the signs of the second equation.

9x + 2y^2 - 3z^2 = 132

-9y - 2y^2 + 3z^2 = +12

You have left 9x - 9y = 144.

Factor out the 9 so you have 9(x - y) = 144

Divide both sides by 9

x - y = 16

User Lila Viollette
by
6.0k points